Giant mesenteric teratoma - Basem Saied Abdelkader; Mahmoud Ahmed Ahmed Abdelbary (Elsevier, 2020)
Mesenteric teratoma is a rare tumor in children. The present case is huge mesenteric teratoma (20 × 20 × 10 cm) and (1.96 kg) arising near the root of mesentery with ileal segment attached to it. Complete surgical excision of the mass with adherent intestinal segment with primary anastomosis. The histopathological examination showed bengin muture teratoma with no atypia or malignancy.